Preventing accidents at traffic junction with obstructed view using V2X (Vehicle-To-Everything) communication - Part 2 - Lee, Terina Shi Min (2018)
This paper wishes to improve road safety conditions by providing vehicles with the ability to connect and communicate wirelessly. This project exploits the use of Vehicle-to-Vehicle(V2V) communication or Vehicle-to-Everything(V2X) communication in vehicles to interact with each other within the communication range. The objective of this application is to transmit and receive any road safety messages to and from neighboring vehicles, which produce warning messages to alert road users of any road emergency which may pose potential threats to the safety of the drivers in the same vicinity. This will require the analysis on Controller Area Network(CAN) messages broadcasted in the CAN bus of each vehicle, to detect any emergency of the principal vehicle. This paper will cover the main communication protocols and standards which are essential in the development of the application to detect Electric Emergency Brake Light(EEBL) event in a vehicle, as well as existing studies about the application of the various communication protocols. The development process of the application will then be discussed by the report, followed by the results and future works of the project. Currently, road safety depends heavily on drivers’ judgements which are restricted to the range of road visibility of the drivers. Thus, this project aims to improve road safety conditions by keeping drivers updated of current road situations which exceeds the visibility range of drivers. This will help drivers to reduce the impact of road emergency, as they are granted a longer reaction time to the situation through V2V communication amongst connected vehicles.